La afectación al mercado laboral por la presencia de trabajadores venezolanos, percibiendo salarios no previstos en la ley en la ciudad de Guaranda en el año 2021. - Guzmán Borja, Elizabeth Alejandra (2023)
Work is an inescapable right, which constitutes a key mechanism in the development process of society. Work allows personal fulfillment and material progress simultaneously, which is why it constitutes the link between social development and economic progress. Until September 2021, approximately 4.3 million people left Venezuela. 80 percent emigrated to Latin America and the main receiving countries have been Colombia, Peru and Ecuador. At the beginning of the Venezuelan exodus, Ecuador was characterized as a transit country to Peru or other countries in the southern cone such as Chile and Argentina. However, between 2015 and September 2020, almost 400,000 Venezuelans decided to settle in Ecuador. The Ecuadorian labor market shows a deterioration in the quality of employment. This was due to the reduction in economic activity after the 2014 oil shock – from which the country never fully recovered – to the urgent need to adjust macroeconomic balances to make public finances sustainable and to the issuance of regulations that tightened labor contracting. Due to their economic condition, Venezuelan migrants often work in less favorable conditions. The proportion of the population with employment is higher for Venezuelans (18 percentage points), but almost 60 percent work in the informal sector, in a temporary job (71 percent) and only 84 percent have received for their work the agreed payment. Added to this is the fact that, on average, Venezuelan workers spend more hours a week at work than Ecuadorians, but receive a lower average monthly payment. The hiring of Venezuelan labor directly affects the labor market, since each Venezuelan worker earns less than a unified basic salary, affecting the jobs for Ecuadorians, who in one way or another are also being affected since the employer he prefers to pay Venezuelan labor for its value.